Association Rules Elicitation for Customer’s Shopping on E-commerce Applications - Bassant Ashri Nouri; Mohamed Saad Gaafar (المجلة الدولية للحاسبات والمعلوماتية, 2024)
This research provides an approach for eliciting association rules for customers’ shopping on e-commerce applications based on the Apriori algorithm. The proposed system shows and displays some offers and deals from various branches. The system provides the analytics for the seller as the demand for some varieties and the weakness in other varieties and the whole application is organized on the Cloud. The architecture includes three levels; the front-end, middle, and back-end. The front-end level of the site-based Mobile shopping application is made up of Android Mobile devices, to buy miscellaneous products from various nearby branches. The front-end level also displays the link between items purchased. The middle repository level provides a Web service to generate returns from a relational database. The Exchanged information and data between application and servers is stored in the Cloud. The background level offers a Web server and a MySQL database. In this paper, we propose an architecture that reduces the communication overhead in existing Mobile Agent-based Distributed Association Rule Mining (MAD-ARM).